Mechanical behavior and constitutive modeling of CO2-foamed carbonated MgO-based solidified slurry under Unconsolidated Undrained (UU) triaxial conditions - Ping Gao; Jinbo Xie; Qinglong You; Xi Du; Li Shao; Weihong Xie (PLoS ONE, 2026)
Geotechnical construction activities, such as shield tunneling and pile foundation construction, generate large amounts of high-water-content waste slurry, making its disposal and resource utilization challenging. This paper introduces a CO 2 -foamed carbonation solidification technique using a composite binder system made of reactive magnesium oxide (MgO), slag, and calcium carbide slag. The mechanical behavior of the lightweight carbonated slurry was investigated through Unconsolidated Undrained (UU) triaxial compression tests under various confining pressures. Quantitative results indicate that the reactive MgO dosage significantly governs strength evolution; an optimum MgO dosage of 10% yielded the highest peak stress of 190.8 kPa (at 50 kPa confining pressure), while the softening coefficient peaked at 0.46 with a 13% dosage. Regarding the CO 2 foam impact, varying the foam content from 36% to 52% resulted in softening coefficients ranging between 0.20 and 0.50. The 36% foam dosage provided the optimal structural stability with a peak stress of 179 kPa, whereas excessive foam leads to greater pore connectivity, worsening strain-softening. Confining pressure significantly affects the material’s hardening and residual strength. Based on these findings, an improved constitutive model was developed using damage evolution and a modified Duncan–Chang framework, providing accurate descriptions of the material’s elastic, hardening, post-peak softening, and residual characteristics. This study advances our understanding of CO 2 -foamed carbonated MgO-based slurry, offering new insights for both solidification/stabilization and carbon sequestration of high-water-content waste slurry.